Pengembangan Multimedia Audio Visual pada Materi Pokok Menulis Puisi Siswa Kelas VII - Evin Etik Sari Zalukhu; Niksapta Debora Waruwu; Putra Rizki Tambunan (Journal on Education, 2023)
In order to create audiovisual materials for Indonesian language classrooms, the researcher employed the Research and Development (R&D) deskriptif kualitatif method. A storyboard is a diagram that organizes information in an audiovisual production. Three things are explained in a storyboard: the plot, the visuals, and the plot summary. The storyboard from this study will serve as a blueprint for creating an instructional film. Using audiovisual media effectively and efficiently in instruction allows for the presentation of student work. This is due to the fact that learning makes for a challenging puisi, harms children, and can address different learner preferences. Temuan ini mengarahkan para peneliti pada kesimpulan bahwa mempelajari cara membuat puisi dan mendorong pembelajaran yang bermakna using material audiovisual. This study calls for increased use of audiovisual media for a few dash-level lessons in Indonesian language instruction.